A new theoretical performance analysis method considering longitudinal and transverse end effects for flat linear induction magnetohydrodynamic pumps - Ding, Ming; Yang, Chunwei; Bai, Yifan; Bi, Keming; Yan, Xin (Frontiers in Nuclear Engineering, 2025)
The flat linear induction pumps (FLIPs) are a class of driving devices that converts electromagnetic energy into mechanical energy of pumped liquid metal, which are widely used in the field of energy power and chemical industries. The end effects and wall eddy current effect of FLIPs can significantly reduce the pump head and energy conversion efficiency. In this paper, the longitudinal and transverse end effects of FLIPs caused by the finite length of the core were analyzed, and the analytical expressions of the electromagnetic field in the electromagnetic air gap were given. Based on the mathematical analysis of the end effects and the T-shaped equivalent circuit of the rotary induction motor, an equivalent circuit model was established, considering two kinds of end effects and wall eddy current effects. The calculation methods of main characteristic parameters, such as head and energy conversion efficiency, were given. The accuracy of the analytical model was validated by comparing the calculation results with the open experimental data. The work can provide a rapid analysis method for improving the energy conversion efficiency and working performance of FLIPs.